Quantitative determination of the solidus line in the dilute limit of succinonitrile-camphor alloys - Mota, F. L. (2016)
Different phase diagram measurements for succinonitrile-camphor alloys to date have yielded different values of the solute partition coefficient and the freezing range of the alloy. These parameters are critical to model solidification microstructure evolution. New measurements are made to precisely characterize the dilute limit of the succinonitrile-camphor phase diagram using thin-sample directional solidification experiments where convection is negligible, so that solute transport in the melt is purely diffusive, and the temperature gradient is constant in time. These results are confirmed through complementary measurements by differential scanning calorimetry and isothermal annealing. Possible measurement uncertainties in previously measured solidus lines are discussed. Experimental results were further confirmed using a boundary layer model of transient planar interface dynamics.